SINAIS E SINTOMAS RESPIRATÓRIOS ASSOCIADOS AO USO DE ANTI-HIPERTENSIVOS: UMA REVISÃO INTEGRATIVA - Orenito Simão Borges Júnior; Cristina Ferreira Lemos; Marcelo Fouad Rabahi (UniEVANGÉLICA, 2015)
Objective: To produce a set of information about the respiratory symptoms occasioned by adverse effects of antihypertensive correlating them with their clinical importance. Methods: Integrative review developed in a descriptive and observational study, based on the analysis of package inserts of antihypertensive drugs registered in ANVISA, discussed by scientific articles that evidencing the clinical application of these effects or the conceptions about the problem. Whereupon the articles were search on electronic basis, published between 2002 and 2014, in the databases: Cochrane Library, MEDLINE, Excerpta Medica, LILACS and SciELO. Results: In the 31 drugs of antihypertensive drug classes covered in the survey, the majority (38.7%) had reactions such as cough and dyspnea as a common side effect. Other effects such as rhinitis and bronchospasm are present in the use of 29% of the drugs, but with lower frequency of symptoms (unusual). Being pronounced such events in inhibiting group angiotensin converting enzyme inhibitors, diuretics subgroups while loop, thiazide and β-adrenergic antagonists (with the exception of Metoprolol) were far safer for therapy in patients with respiratory problems. Final consideration: The results presented shows worrying about the treatment of hypertension, especially when it comes to selection of hypotensive agents in patients with asthma, Chronic Obstructive Pulmonary Disease or other respiratory conditions. In addition, the results shows that cough and nasal obstruction, commonly associated with various diseases, and described as one of the most frequent causes of seeking medical care may be associated with adverse effects of medication.